Effects on Powdery Mildew and the Mutualistic Fungal Endophyte Epichloë gansuensis When Host Achnatherum inebrians Plants Are Sprayed with Different Fungicides - Yue Zhu; Keke Cao; Kelin Wu; Michael J. Christensen; Jianxin Cao; Yanzhong Li; Xingxu Zhang; Zhibiao Nan (Agriculture)
A study was conducted to examine the effects of the spray application of nine antifungal products, including microbial-derived fungicides, plant-derived fungicides, and chemical fungicides, on the grass Achnatherum inebrians that was either host to Epichloë gansuensis (E+) or E. gansuensis-free (E−) and that was exposed to Blumeria graminis, the fungal pathogen causing powdery mildew. The Epichloë endophyte is a seed-borne mutualistic biotrophic fungus whose growth is fully synchronized with the host grass. Bl. graminis is a biotrophic pathogen that continually infects leaves and stems via conidia, the formation of appressoria, leading to the presence of haustoria in epidermal cells. Prior to fungicide application, the presence of endophytes significantly increased the resistance of A. inebrians to powdery mildew and was able to increase the chlorophyll content. However, the positive effects of the Epichloë endophyte on the plant were suppressed with the use of some fungicides and the increase in the number of sprays, but the reciprocal relationship between the Epichloë endophyte and the plant was not significantly disrupted.